TECHNO-ECONOMIC ASSESSMENT OF A GRID-CONNECTED WIND POWER PLANT IN WESTERN AFGHANISTAN - Hikmatullah Mayar (Journal Of Renewable Energy Engineering, 2026)
Afghanistan suffers from chronic electricity shortages, currently importing approximately 70% of its power from neighboring nations. This research presents a techno-economic evaluation of a utility-scale, grid-connected wind power plant in the Zinda Jan district of Herat province. Utilizing wind speed data from the Global Wind Atlas and optimization via HOMER Pro software, the study identifies a robust wind regime with average annual speeds reaching 7.25 m/s at a 100 m hub height. The proposed 5 MW configuration achieves an annual electricity generation of approximately 29.25 GWh with an exceptional capacity factor of 66.8%. Economically, the project demonstrates a simple payback period of eight years and a Net Present Cost (NPC) of $14.0 million. These results suggest that localized wind power can significantly enhance energy security and reduce reliance on fragile import chains.